Correlation of Trividha Pariksha with Chaturvidha Pramana: A Review Article - Devi, Riyanka; Mahant, Vividha; Chauhan, Meenakshi; Kumari, Abhilasha; Bala, Madhu (International Research Journal of Ayurveda & Yoga, 2024)
In Ayurveda, the word “Pariksha” is used for Pramana. Pariksha is composed of two words “Pari” means “all around” and “iksha” means “to inspect or view.” The synonyms of Pariksha are Pramana, Saadhana, Jynana, and Uplabdhi. Any abnormality in the normal structural or physiological aspect of the body develops a disease. For proper treatment of the disease, proper diagnosis is a must. Before treatment of the disease, an examination is necessary. Examination of disease can be done with the help of Trividha Pariksha, that is, – Darshana, Sparshana, and Prashana. Pariksha helps in understanding the condition of the patient. Trividha Pariksha is done by the method of Chaturvidha Pramana, that is, Aaptopdesha, Pratyaksha, Anumana, and Yukti which tell the object truly.